(3GdeNGWQ h SHd GdehGLgI s - (3hOjY (B, (3GdYRYRj s ((3YeGf (B:s (3OGQ GdMGeO(B,s, 2019)
(3GSJYQV GdcJGH aj GdaUd GdChd(B: (3eG gj GdTGFYGJ, hCgOGagG, hNUGFUgG, hCfhGYgG heQGMd JchjfgG, hYhGed GfJTGQgG, ef NdGd eHMKjf, HjfeG JfGhd GdaUd GdKGfj(B: (3THcGJ GdJhGUd GdGLJeGYj eaghegG heejRGJgG hCfhGYgG hJCKjQGJgG ef NdGd eHMKjf, ajeG fGbT GdaUd GdKGdK(B: (3hGbY GdTGFYGJ aj THcGJ GdJhGUd GdGLJeGYj hYdGbI ehGbY GdJhGUd GdGLJeGYj HGdTGFYGJ, hOhQ THcGJ GdJhGUd GdGLJeGYj aj fTQ GdTGFYGJ, hBdjGJ fTQgG heUGOQgG, HGdEVGaI Edi ghjI GdaQO aj THcGJ GdJhGUd GdGLJeGYj ,CeG aj GdaUd GdQGHY JWQb Edi eNGWQ GdTGFYGJ hSHd GdehGLgI ef NdGd eHMKjf; NUU GdeHMK GdChd dJMdjd eNGWQ GdTGFYGJ hJCKjQGJgG Ydi GdeLJeY, hGdeHMK GdKGfj ddMOjK Yf SHd ehGLgI GdTGFYGJ aj THcGJ GdJhGUd GdGLJeGYj(B.s
(3HjHdjhZQGajG U(B.117s
Keywords: (3GdGYdGes; (3GdGfJQfJs; (3GdTGFYGJ s